Rancang Bangun Sistem Klasifikasi Kualitas Minyak Goreng berdasarkan Warna dan Kejernihan menggunakan Metode Naive Bayes berbasis Arduino Uno - Joan Chandra Kustijono; Fitri Utaminingrum; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Cooking oil is one of the basic needs of the Indonesian people for food processing ingredients, especially for frying process. Palm cooking oil is commonly used by Indonesian people because it matches the Indonesian people's taste. In its use, cooking oil is often used repeatedly for savings which is known as used cooking oil. The use of used cooking oil can increase the risk of several diseases for the body, such as carcinoma and diarrhea caused by the accumulation of peroxide values, as well as changes in the color and clarity of the oil. To determine the quality of the oil, the method used today is to test the peroxide number in the laboratory. However, this method takes more time and is not cheap. So that a system was created that can detect the quality of cooking oil based on color and clarity using the Naive Bayes method to shorten the time at a lower price. This study uses a TCS3200 sensor to detect color changes, and an LDR sensor to detect oil clarity. There are 2 classes used, namely the Eligible class to declare that the oil is still suitable for use and the Inappropriate class to declare that the oil is not suitable for use. In the research results, the accuracy of the TCS3200 sensor is 95.15%, the accuracy of the Naive Bayes method is 87,5%, and the overall system accuracy is 87.5%.